PERAN KECERDASAN BUATAN DALAM DUNIA PENDIDIKAN DI ERA ARTIVICIAL INTELLEGENCI ( AI ) PADA SDN INPRES DOYO LAMA - Dike, Yosina; Satyawati, Sophia Tri; Wasitohadi, Wasitohadi (Consilium: Education and Counseling Journal, 2025)
This research aims to identify the challenges and opportunities in implementing artificial intelligence (AI) at SDN Inpres Doyo Lama. Through a qualitative approach, this study involved in-depth interviews with teachers, students, and the school principal. The results showed that the main constraints in implementing AI were the lack of adequate infrastructure, as well as the limited knowledge and skills of teachers in utilizing AI technology. However, this study also identified the great potential of AI in improving the quality of education, especially in terms of personalized learning and access to a wider range of learning materials. "Teachers at SDN Inpres Doyo Lama, like teachers at other elementary schools, are often burdened by a heavy workload of administrative tasks. From creating lesson plans, grading student assignments, managing grades, to creating reports, all of these tasks consume a significant amount of time. As a result, the time that should be used to interact directly with students and develop teaching materials is reduced. Artificial Intelligence (AI) offers innovative solutions to address this problem. By utilizing various AI-based applications, teachers can automate some routine administrative tasks."